2005
DOI: 10.1002/elan.200503283
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Polymerized Polyaniline Films for the Mass‐Production of Biosensor Devices

Abstract: The widespread use of screen-printed electrodes in biosensor applications has meant that mass-production of disposable, inexpensive sensors has become feasible. However, the complexity of surface coatings that require difficult and time-consuming deposition procedures do not lend themselves to the same production conveniences. This article describes moves towards the development of an alternative to the electrochemical deposition of polyaniline on electrode surfaces for incorporation into an established sensor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 16 publications
(19 reference statements)
0
10
0
Order By: Relevance
“…Consequently, electrochemical polymerisation does not comply with the requirements of mass-production, especially of single-use sensor devices, with authors of the opinion that cyclic voltammetry is not a suitable deposition technique for industrial applications of PANI [28]. A chemical method of polymerisation has also been investigated in our laboratory, to assess its feasibility as a component of an established biosensor system [29]. Such a method would enable a greater number of electrodes to be prepared in situ without the need for instrumental techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, electrochemical polymerisation does not comply with the requirements of mass-production, especially of single-use sensor devices, with authors of the opinion that cyclic voltammetry is not a suitable deposition technique for industrial applications of PANI [28]. A chemical method of polymerisation has also been investigated in our laboratory, to assess its feasibility as a component of an established biosensor system [29]. Such a method would enable a greater number of electrodes to be prepared in situ without the need for instrumental techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the oxidized reaction was performed immediately at 700 mV (vs. Ag/AgCl) for 1500 s. In the oxidation process, HRP would electrostatically attach to the PANI surface. 18 Eventually, the TEMC was completed as a H 2 O 2 biosensor for use in subsequent experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Asberg and Inganas have cross-linked horseradish peroxidase in highly conducting poly(3,4-ethylene dioxy thiophene) (PEDOT)/(polystyrene sulphonate) (PSS) dispersion using poly-4-vinylpyridine for estimation of hydrogen peroxide [124]. Grennan et al have reported the horseradish peroxidase immobilized screen-printed electrodes based on chemically polymerized polyaniline/polyvinylsulphonate films, which can be used for the mass production of biosensors [125]. Jia et al have fabricated horseradish peroxidase (HRP) biosensor by self-assembling gold nanoparticles to a thiol-containing sol-gel network of 3-mercaptaopropyltrimethoxysilane (MPS) [126].…”
Section: Enzymosensorsmentioning
confidence: 99%